Cutting properties of deposited amorphous silicon in ultra-precision machining. (13th June 2018) - Jelenković, Emil V; To, Suet; Chen, Ling; Xiao, Gaobo; Zhao, Zejia; Tang, Chak Yin
Abstract: The widely used amorphous silicon material is often a deposited one. It is mainly applied in the electronic industry and shows to be a promising candidate for optical devices. The mechanical cutting of deposited amorphous silicon has not been reported so far, while ultra-precision machining of such material for optical devices can be superior to a lithographic approach. In this article, for the first time, cutting properties of deposited amorphous silicon are compared with those of single crystal silicon and polycrystalline silicon, using plunge cut experiment. It is found that the critical depth of cut (CDC) and cutting forces for the amorphous silicon are close to those of single crystalline silicon in the easy-to-cut orientation. In comparison to the polycrystalline silicon, amorphous silicon has higher CDC and lower cutting force. This may allow machining of amorphous optical devices on different semiconductors and/or moulds on various materials with enhanced and isotropic CDC, reduced tool wear and simplified cutting control.